Dossier III: Suicidio: Una realidad oculta en la guardia civil - Argudo, Aarón (Quadernos de criminología, 2022)
The phenomenon of suicidal behavior stems from a complex psychological situation with fatal consequences. In the police field it has caused social alarm, specifically, in the Civil Guard, it seems that suicide rates are higher than in the Spanish reference population, which is the basis of this work. The results show worrying data that allow us to conclude emphatically, a more harmful behavior among the Civil Guard agents.